The impact of training module, training method, and competent trainer on employee performance at oil and gas industry in Malaysia - Thamilarasan, Subdrarajan (2025)
This study examines the impact of training modules, training methods, and trainer competencies on employee performance within Malaysia's oil and gas industry. Using a quantitative survey approach, the research explores how these factors contribute to the effectiveness of training programs and their subsequent influence on workforce productivity. The correlation analysis revealed positive relationships between all three variables and employee performance; however, regression analysis found that training modules and methods were not statistically significant predictors of performance (p > 0.05). In contrast, the competency of trainers was found to be a significant predictor of employee performance (β = 0.617, p < 0.001). This highlights the critical role that trainers play in enhancing employee performance, particularly through effective communication, motivation, and the application of practical skills. The findings suggest that while well-designed training modules and methods are important, they must be complemented by skilled trainers who can facilitate the practical application of knowledge. The study offers valuable insights for HR managers and industry leaders, recommending that organizations prioritize continuous professional development for trainers to ensure the optimal delivery of training programs. These findings contribute to the development of more effective human resource strategies aimed at improving employee performance and maintaining a competitive edge in the dynamic oil and gas sector